LINGUISTIK KORPUS KUANTITATIF DAN KAJIAN SEMANTIK LEKSIKAL SINONIM EMOSI BAHASA INDONESIA - Gede Primahadi Wijaya Rajeg (Linguistik Indonesia, 2020)
This paper demonstrates the application of Multiple Distinctive Collexeme Analysis (MDCA) to study nuances and similarity between HAPPINESS near-synonyms in Indonesian. MDCA, as a variant of a family of quantitative corpus linguistic method called Collostructional Analysis, is proposed as a usage-based operationalisation for a classic theoretical construct in cognitive linguistic approach to emotion semantics, namely the idea of “related concepts” associated with the meaning of an emotion. Using MDCA, I expanded the idea of “related concepts” to investigate the semantics of more than one, near-synonymous, emotion on the basis of the synonyms’ distinctive collocates. I argue that MDCA (i) provides empirical basis for such a theoretical idea as “related concepts” and (ii) helps enrich semantic characterisation of a given emotion word in comparison to its synonyms, highlighting how they may differ or converge semantically.